Sufistic Curriculum Development Management at the Islamic Boarding School - Aji Muhammad Iqbal; Adang Hambali; Bambang Syamsul Arifin; Asep Achmad Hidayat (International Journal of Islamic Educational Research, 2025)
The research departs from the phenomenon of the development of Islamic boarding school education models with varying names and styles. Islamic boarding schools are faced with two important problems in adapting to the demands of the times, namely the problem of developing Islamic boarding school governance without abandoning tradition and the Islamic boarding school's identity in producing a generation with good morals. The research objectives are to identify the management of Sufistic curriculum development in Islamic boarding schools including; 1) Curriculum planning, 2) Curriculum organization, 3) Curriculum implementation, 4) Curriculum evaluation and 5) Impact of Islamic boarding school management in developing the Sufistic curriculum at Al-Istiqomah Islamic Boarding School and Al-Falah Biru Islamic Boarding School, Garut Regency. The research framework departs from George R. Terry's (1973) management theory, namely four management functions, namely: 1) Planning, 2) Organizing, 3) Actuating, 4) Controlling. The curriculum theory uses the Ralph W curriculum development model. Tyler curriculum development is carried out in systematic stages, namely; Objectives, Selecting Learning Experiences, Organizing Learning Experiences, Evaluation. Developing the Islamic boarding school curriculum has an impact on the morals of the students, as according to Sheikh Musthafa Al-Ghalayini, the implications of Sufistic moral values contribute to shaping behavior. This study uses a qualitative approach using the Ethnography method. Data collection techniques are carried out through interviews, observations and documentation analysis. The data analysis technique uses the Miles and Huberman analysis technique. While the validity test is carried out with data validity by conducting tests; credibility, transferability, dependability, and confirmability. The results of the study found that the management of the development of the Islamic boarding school curriculum in preparing a generation with Sufi morals: First, the Islamic boarding school curriculum is included in the traditionalist model of the school, namely by showing its traditional and school character. Second, the organization of the curriculum content consists of the contents of the curriculum, data, concepts, generalizations, and subject matter at the Islamic Boarding School. Third, Curriculum development is categorized as a grass roots model where there are initiatives and efforts coming from below, namely ustadz and Islamic boarding schools in developing a curriculum that is designed by themselves to produce a generation with Sufi morals. Fourth, Curriculum evaluation refers to the Objective Model Evaluation model (objective model) carried out at the end of curriculum development, this assessment activity is often called summative evaluation. Fifth, The impact of curriculum management on the level of morals is shown by the nature of istiqomah, self-control, prioritizing Islamic and basyariyah brotherhood, tolerance, honesty, sincerity, istiqomah, patience, gratitude, politeness and helping each other. Sixth, Traditionalist Hypothetical Management Model of the School.